A Study on the Effects of 16-Week Taiji Cardiac Rehabilitation Program in Reducing Psychological and Physiological Stress in Patients with Coronary Heart Disease - Cui, Meize; Zhang, Jianwei; Li, Yameng; Wei, Qiuyang; Li, Lujia; Huang, Yuerong (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details